Social inclusion and mental health - Boardman, Jed ca. 20./21. Jh; Killaspy, Helen ca. 20./21. Jh; Mezey, Gillian ca. 20./21. Jh (Cambridge medicine (Series), 2023)
People with mental health conditions are among the most socially excluded groups in society. Mental health conditions are influenced by the social environment, which in turn shapes our social and cultural responses to the people who experience them. Much of what mental health practitioners do is 'essentially social' and the effects of their interventions are hampered by the marginalised status of many of the people that they see. This book documents the ways in which people with mental health conditions are excluded from participating in society and offers some pointers as to how this may be reversed. It highlights the need to reduce mental health inequalities and to consider the importance of material inequalities and social injustices faced by people experiencing mental ill-health. Whilst the challenges are considerable and the solutions wide-ranging, mental health practitioners can play a significant role in facilitating the social inclusion of those with mental health conditions